Vaccination Status and Symptom Severity in Covid-19 Patients - Nisrina Anggraeni; Titik Kuntari (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
We are still attempting to reduce COVID-19 morbidity and mortality through several means, including immunization. In early December 2021, Indonesia had 49.19% coverage of the second COVID-19 vaccination. Researching and collecting data on the association between vaccine completion and symptom severity is critical to persuade individuals to vaccinate. This study aims to examine the relationship between COVID-19 vaccination status and the degree of symptom severity in COVID-19 patients. This cross-sectional study used secondary data from the medical records of COVID-19 patients at the PDHI Yogyakarta Islamic Hospital from June to October 2021. The